A literatura odepórica e a peregrinação jacobea: um estudo sobre a espiritualidade nos relatos de viagem dos peregrinos brasileiros no Caminho de Santiago - Nogueira, Paulo César Giordano (2008)
This study aims at outlining a profile of the Brazilian pilgrim. Its major concern is the pilgrim s spirituality the way it shows in the path to Saint James of Compostela, the ancient medieval pilgrimage path. The sources of our research are the narratives of Brazilian pilgrims who, after having walked the Way of Saint James, published their experiences in works classified as hodoeporic literature, travel narratives. Our hypothesis is that, despite some may consider that the jacobean route has been losing its main characteristic, to wit, the Christian message and the religious attitude expected from this kind of phenomenon, there is a huge number of pilgrims that keep its spiritual tradition alive during their journey. Thus, born within a remarkable religious context, the pilgrimage still implies the practice of religious and spiritual disposition of contemporary pilgrims, reaching far beyond tourism business exempt from spiritual values